Seismic safety evaluation of concrete dams a nonlinear behavioral approach - Jin, Feng; Wang, Jinting; Xu,, Yanjie (Butterworth-Heinemann, an imprint of Elsevier, 2013)
The consequences of a large dam failing can be disastrous. Based on a nonlinear approach, this title allows engineers to build models that account for nonlinear phenomena such as vertical joint slippage, cracks, and cavitation. It includes nonlinear fracture of dam-water-foundation interaction system, dynamic fluid-structure